(untitled) (Journal of the College of Basic Education, 2022)
The results of the study indicated that infection with soybean mosaicism led to a significant reduction in the number and weight of bacterial nodules, in addition to a reduction in the dry weight of the seeds. The percentages of reduction were calculated on the basis of the comparison treatment.